Possessed [compact disc, unabridged] - Dostoyevsky, Fyodor, 1821-1881 (Everyman's library, 2009)
The Possessed depicts the destructive chaos caused by outside agitators who move into a provincial town. The enigmatic Stavrogin dominates the novel. His magnetic personality influences his tutor, the liberal intellectual poseur Stepan Verhovensky, and the teacher's revolutionary son Pyotr, as well as other radicals. Stavrogin is portrayed as a man of strength without direction, capable of goodness and nobility. When Stavrogin loses his faith in God, however, he is seized by brutal desires he does not fully understand.